Magnetic susceptibility record of loess/paleosol sequence: Case study from south-west Slovakia - ĎURŽA, Ondrej; DLAPA, Pavel (Contributions to Geophysics and Geodesy, 2009)
The paper  proposes a new method to distinguish between  paleosols and glacial loess deposits. The  aim  of our study is to test whether magnetic susceptibility measure- ments can be used as proxies for determining the boundary between the loess and paleosol. The  measurements show excellent correlation with  occurrence of the horizons  inﬂuenced with  pedogenesis. These  values are generally  explained in terms of the greater concentra- tions  of ultraﬁne ferrimagnetic minerals  in the recent  soils and  paleosols.   The  observed relationship between  the susceptibility  and  lithology   follows  the behavior observed  on the  Chinese  Loess Plateau, which  is the  complete opposite  of the pattern reported from Alaskan and  Siberian  loess deposits.